2022
DOI: 10.3389/fpls.2022.994314
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene emitted by viral pathogen-infected pepper (Capsicum annuum L.) plants is a volatile chemical cue that attracts aphid vectors

Abstract: Plant viruses are obligate intracellular pathogens, and most depend on insect vectors for transmission between plants. Viral infection causes various physiological and metabolic changes in host traits, which subsequently influence the behavior and fitness of the insect vectors. Cucumber mosaic virus (CMV), one of the most widespread pathogens in pepper (Capsicum annuum L.), is transmitted by aphid vectors in a non-persistent manner. Here, we examined whether CMV infection in pepper affects the behavior of aphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…For example, virus‐induced plant volatiles such as green leaf volatiles, sesquiterpenes and terpenoids manipulated non‐viruliferous insect vectors to prefer virus‐infected plants over virus‐free plants 8–10 . Likewise, more ethylene was released by cucumber mosaic virus (CMV)‐infected pepper plants, which acted as an attractant odor cue to insect vectors (aphids) 11 . Plant volatiles which act as repellents to insect vectors can be repressed by plant viruses, leading to insect vectors showing a preference for virus‐infected plants 12–15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, virus‐induced plant volatiles such as green leaf volatiles, sesquiterpenes and terpenoids manipulated non‐viruliferous insect vectors to prefer virus‐infected plants over virus‐free plants 8–10 . Likewise, more ethylene was released by cucumber mosaic virus (CMV)‐infected pepper plants, which acted as an attractant odor cue to insect vectors (aphids) 11 . Plant volatiles which act as repellents to insect vectors can be repressed by plant viruses, leading to insect vectors showing a preference for virus‐infected plants 12–15 .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Likewise, more ethylene was released by cucumber mosaic virus (CMV)-infected pepper plants, which acted as an attractant odor cue to insect vectors (aphids). 11 Plant volatiles which act as repellents to insect vectors can be repressed by plant viruses, leading to insect vectors showing a preference for virus-infected plants. [12][13][14][15] However, the majority of these findings primarily focus on the role of plant volatiles in mediating interactions among host plants, plant viruses and insect vectors.…”
Section: Introductionmentioning
confidence: 99%
“…Using fluorescently tagged viruses, we showed that CMV and BBWV2 synergistically interact when coinfecting a plant host: (i) the enhancement of the CMV cell-to-cell movement in upper young leaves (thereby, the two viruses infect the same leaf areas); (ii) an increase in BBWV2 accumulation; (iii) an increase in symptom severity; and (iv) active replication in the same cells without spatial interference. This synergism in CMV and BBWV2 infection dynamics might be linked to their transmission dynamics because both viruses can be transmitted by the same aphid vectors 39,40 . Previously, field surveys have reported that CMV and BBWV2 are highly prevalent in pepper fields in South Korea and that the incidence of mixed infection by the two viruses is higher than 50% 3,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Broad bean wilt virus 2 (BBWV2; genus Fabavirus, family Secoviridae) that commonly co-infects crop plants with CMV is another prevalent virus in pepper fields in South Korea 3,38 . Both CMV and BBWV2 are transmitted by aphids in a non-persistent manner 39,40 . Previous field surveys showed that more than 50% of the collected pepper samples were mixedinfected with CMV and BBWV2, and this double infection caused more severe damage in pepper plants than single infection with each virus through synergistic symptom expression 3,38 .…”
mentioning
confidence: 99%
“…For instance, VOCs such as GLVs, sesquiterpenes, and terpenoids induced by cucumber mosaic virus (CMV), BYDV, and potato leaf roll virus (PLRV) attracted non-viruliferous insect vectors to feed virus-infected plants over virus-free plants [ 6 , 12 , 13 ]. Myzus persicae and Aphis glycines preferred CMV-infected pepper plants to CMV-free pepper plants, due to the CMV-infected pepper plants emitting more ethylene than CMV-free pepper plants [ 14 ].…”
Section: Introductionmentioning
confidence: 99%